Energy security, poverty and vulnerability in Central Asia and the wider European neighbourhood - Ben Slay (Center for Social and Economic Research (CASE), 2009)
This paper seeks to disaggregate concerns about energy security within the wider European neighbourhood from the nation-state to the household, and particularly to poor households in the transition and developing economies of the former Soviet Union. It argues that two decades of under-investment in Soviet-era energy, water, and communal service infrastructures threaten significant reductions in access to these services in the poorer countries of this region, particularly Tajikistan and Kyrgyzstan. These problems are manifesting themselves both in terms of growing physical restrictions on access to energy, water, and communal service networks in these countries, and in terms of rapid growth in tariffs for these services which could price some vulnerable households out of the market”. The paper also suggests that these problems are apparent to various degrees in a number of other former Soviet republics, and that the impact of the global economic crisis is likely to exacerbate these problems. By calling attention to growing household vulnerability to energy and water insecurities, particularly in Central Asia, the paper seeks to bring an economic development perspective to bear on energy policy debates in the wider European region.
Keywords: I32; P28; L43; P36; 330; legal monopolies; regulation; deregulation; energy; environment; transition; welfare; consumer economics; poverty; health; education; training; Energieversorgung; Versorgungswirtschaft; Kommunale Versorgungswirtschaft; Infrastruktur; Erneuerbare Energie; Wirtschaftskrise; Armut; Privater Haushalt; Zentralasien; Europa